1995
DOI: 10.1074/jbc.270.27.16198
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Glycosaminoglycan-binding Protein Is the Vertebrate Homologue of the Cell Cycle Control Protein, Cdc37

Abstract: Using a monoclonal antibody, IVd4, that recognizes a novel group of hyaluronan-binding proteins, we have immunoscreened a cDNA library constructed from embryonic chick heart muscle mRNA. One of the cDNAs isolated from the library encodes a 29.3-kDa protein homologous to Cdc37, an essential cell cycle regulatory factor previously characterized genetically in yeast and Drosophila; this is the first vertebrate CDC37 gene to be cloned to date. We also present evidence for the existence of a second chick isoform th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 58 publications
2
84
0
1
Order By: Relevance
“…Recently, a chicken homologue of Cdc37, known to influence the activity of p34 ~a kinase in cell cycle progression is also shown to bind hyaluronic acid, heparin and chondroitin sulfate, suggesting the role of GAG binding protein in cell division control (28). Thus, the present observation documents the role of 34 kDa HA-binding protein in HA induced cellular signalling, in addition to the reported involvement of CD44 (3,4), RHAMM (5) and Cdc37 (28).…”
Section: Mitogensupporting
confidence: 47%
See 1 more Smart Citation
“…Recently, a chicken homologue of Cdc37, known to influence the activity of p34 ~a kinase in cell cycle progression is also shown to bind hyaluronic acid, heparin and chondroitin sulfate, suggesting the role of GAG binding protein in cell division control (28). Thus, the present observation documents the role of 34 kDa HA-binding protein in HA induced cellular signalling, in addition to the reported involvement of CD44 (3,4), RHAMM (5) and Cdc37 (28).…”
Section: Mitogensupporting
confidence: 47%
“…Thus, the present observation documents the role of 34 kDa HA-binding protein in HA induced cellular signalling, in addition to the reported involvement of CD44 (3,4), RHAMM (5) and Cdc37 (28). In this regard, it is important to mention that the sequence analysis of 34 kDa HA-binding protein already revealed the consensus substrate phosphorylation sites for protein kinases like PKC and CKII (8), highlighting its possible role in signalling.…”
Section: Mitogenmentioning
confidence: 82%
“…Northern analysis revealed that the radio-labeled clone 11 DNA could not detect RNA both in 3Y1 and SR-3Y1 cells, indicating that the REC11 DNA does not correspond to the exon sequence. Recently, Grammatikakis et al identified and characterized the chicken homolog of Cdc37 (CCdc37) [2]. Interestingly, CCdc37 could associate with glycosaminoglycan (GAG) and the putative GAG-binding domains were conserved among Cdc37 of different species (chicken, Drosophila and yeast).…”
Section: Resultsmentioning
confidence: 99%
“…N17 mRNA level begins to be increased in the late G1 and the same level was retained until just before the G2/M transition, suggesting the cell cycle-regulatory role(s) of N17 gene product in mammalian cell systems [1]. Interestingly, Grammatikakis et al have cloned a chicken homolog of Cdc37 (CCdc37), as one of the members which can associate with glycosaminoglycan (GAG) [2]. The nucleotide sequence (306-1047) of N17, which corresponds to the coding region of CCdc37, is 80% identical to the chicken sequence.…”
Section: Introductionmentioning
confidence: 99%
“…In this perspective, the interaction of HABP1 with LBR may also facilitate the process of chromosomal organization during mitosis. Cdc37 is a protein, which has been characterized as a hyaladherin in chicken and as an essential cell cycle regulatory protein in yeast and Drosophila [22]. The role of HABP1 in cell-adhesion is well established and in combination with HA, it might facilitate the process of adhesion and de-adhesion during mitotic stages.…”
Section: Resultsmentioning
confidence: 99%